OC61 A systematic review of serum biomarkers in neonatal encephalopathy to predict short term outcome. (June 2019) - O'Dea, Mary; Hurley, Tim; Mockler, David; Kyng, Kasper; Bob, Phillips; Molloy, Eleanor
Abstract : Background: Neonatal Encephalopathy (NE) describes central nervous system dysfunction from all causes and has a multifactorial aetiology. NE is difficult to diagnose, to treat and to predict outcome. Early prognostic information is important to initiate early intervention of therapies, to counsel parents and to redirect care. There is no gold standard early biomarker to predict outcome at present. Methods: The review protocol was prospectively registered with Prospero. A comprehensive search with relevant search terms of online databases Em Base, PubMed, Cochrane and Web of Science for Biomarkers in Neonatal Encephalopathy to Predict outcome was performed. The short term outcomes examined include severity of Neonatal Encephalopathy, MRI brain and survival in the neonatal period. Two independent reviewers used Covidence software to select the studies. Quality assessment was performed using Cochrane Collaboration Tool for Risk of Bias Assessment and quantitative analysis was completed using Revman software (5.3). Results and Discussion: 1613 papers were identified after duplicates were excluded, and narrowed to 314 papers following abstract review for full text examination. Following full text review 107 papers were included to examine serum biomarkers to predict short term outcome. Raised mean serum levels of IL-6 (p value 0.04, 95% CI -44.5 to -0.66) and lactate (p value <0.001, 95% CI -6.19 to -2.81) are associated with worse short term outcome in NE. The large confidence intervals, however, reflect the small number of studies included and consequently the small population cohorts. Multiple other meta-analyses had substantial heterogeneity and were not statistically significant. A large proportion of studies were excluded due to variety of measured outcomes and methods of data reporting. Establishment of Core Outcomes in NE will benefit future research.